Monitoring athlete health - overtraining, sleep and the immune system - Halson, S. (Journal of Science and Cycling, 2017)
Illness in athletes affects their ability to both perform and train. Through training periods the prevalence of illness is estimated at 4-7%. During the Summer and Winter Olympic Games the prevalence of illness is approximately 7% with studies recommending preventive strategies targeting the greatest risks. The most prevalent system to be affected is the respiratory system with incidence ranging from 41-63% of illness presentations.